Cerebral benzodiazepine receptors in depressed patients measured with [ 123i]iomazenil SPECT - Kugaya, Akira; Sanacora, Gerard; Verhoeff, Nicolaas P.L.G; Fujita, Masahiro; Mason, Graeme F; Seneca, Nicholas M; Bozkurt, Ali; Khan, Shaukat A; Anand, Amit; Degen, Kathleen; Charney, Dennis S; Zoghbi, Sami S; et al. (Biological psychiatry (1969), 2003)
A recent magnetic resonance spectroscopy (MRS) study revealed low γ-aminobutyric acid (GABA) levels in the occipital cortex of depressed patients. No in vivo study has been reported to measure postsynaptic GABA receptors in the patients. Cortical benzodiazepine (BZ) binding to GABA A receptors was measured with [ 123I]iomazenil and single photon emission computed tomography in unmedicated patients with unipolar major depression ( n = 13) and healthy subjects ( n = 19). Group differences were evaluated by means of statistical parametric mapping (SPM) with partial volume correction for gray matter. Occipital GABA levels were determined by proton MRS in a subgroup ( n = 6) of the patients. No evidence of altered BZ binding was found in patients with depression compared with healthy control subjects in the SPM analysis. Although reduction in gray matter volume was observed in the frontal cortex and amygdala of the patients, partial volume correction of the atrophy did not change the result of unaltered BZ binding. GABA levels were found lower in the occipital cortex; however, BZ binding did not show significant relationship to GABA levels. GABA A receptor binding measured in vivo with BZ radioligand binding are not altered in patients with depression.